Flexible sensing probe for the simultaneous monitoring of neurotransmitters imbalance - Cha, Hye Bin; Zhang, Yao; Yu, Hyun-Yong; Lee, Yi Jae (Springer, 2024)
Simultaneous detection of multiple neurotransmitters and their related activities is crucial for enhancing our understanding of complex neurological mechanisms and disorders. In this study, we developed a flexible, high-sensitivity multi-electrodes array probe capable of concurrent detection of four neurotransmitters: dopamine, serotonin, acetylcholine and glutamate. The probe was fabricated on a polyimide substrate with 16 circular gold-film electrodes. These electrodes were modified with PEDOT/GluOx and PEDOT/ChOx for enzymatic detection of glutamate and acetylcholine, and with rGO/PEDOT/Nafion for the detection of dopamine and serotonin. Our electrochemical sensor achieved sensitivities of 184.21 and 219.29 μA/μM cm2 for glutamate and acetylcholine, respectively, with limits of detection (LOD) of 0.0242 and 0.0351 μM within a concentration range of 0.1？100 μM. For dopamine and serotonin, the sensor showed sensitivities of 195.9 and 181.2 μA/μM cm2, respectively, with LOD of 0.4743 and 0.3568 μM. This research advances the field of neurochemical sensing and provides valuable insights into the balance of neurotransmitters associated with neurological disorders. These insights improve diagnostic and therapeutic strategies.